Water quality study of water intake in Asajaya water treatment plant - Alvina, Grifin. (Universiti Malaysia Sarawak (UNIMAS), 2009)
This study was conducted to determine the water quality of Asajaya water intake in Kota Samarahan through physico-chemical parameters. Fifteen water quality parameters were measured which includes temperature, pH 00, salinity, turbidity. conductivity, TDS, ORP, nitrate, ammonia-N, orthophosphate, COD, TSS, chlorophyll-a and BODs. Measurement of physico-chemical parameters were carried out from August 08' January 09' at 3 different ites. ANOV A analysis shows that there were no significant differences in water quality parameters among the 3 sites of sampling except for orthophosphate, BODs, TSS, DO, temperature and nitrates. However. there were significantly differences in water quality parameters among the six months. The mean physico-chemical parameters for temperature (25.68 0c), pH (5.01), DO (3.10 mg/L), salinity (0.01 PSU), turbidity (66.24 NTU), conductivity (4.62 mS m-I), TDS (0.04 giL), ORP (231.04 mY), nitrate (0.02 mglL), ammonia-N (2.00 mg/L), orthophosphate (0.48 mglL), COD (72.84 mg/L), chlorophyll-a (1.23J.lg/L), TSS (1.54 mglL), and BODs (1.19 mg/L). The average of WQI calculated in Asajaya water intake was 57 which corresponds to moderately polluted.